1976
DOI: 10.1002/1098-2337(1976)2:1<39::aid-ab2480020106>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced social docility in male hooded rats by dermal cautery of the vibrissal pads

Abstract: Ablation of the vibrissal pads in rats causes subsequent deposition of scar tissue with little or no regrowth of the vibrissae. Cauterized and intact mature male Long Evans rats were tested for shockelicited fighting, mouse killing, and colony intrusion forms of laboratory‐induced aggression. The results revealed that only conspecific social fighting is blocked by ablation of the major vibrissal follicles. Although no significant group differences were noted in tests for mouse killing, shock‐elicited paired fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

1977
1977
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
11
2
Order By: Relevance
“…These experiments demonstrate that trigeminal somatosensation is critical for the initiation and normal execution of maternal aggression in lactating rats, regardless of previous experience with the treatment or with fighting. Our results extend to maternal aggression in rats previous findings on hypothalamically induced biting in cats (MacDonnell & Flynn, 1966) and on shock-induced fighting (Thor, 1976;Thor & Ghiselli, 1975a;Thor et al, 1974), apomorphineinduced group fighting (Thor & Ghiselli, 1975b), and mousekilling (Gregoire & Smith, 1975;Thor & Ghiselli, I975b;Welle & Coover, 1978) in male rats. Trigeminal desensitization, either acutely with local anesthesia (Thor & Ghiselli, 1975a, 1975bThor et al, 1974;this report) or chronically with lesions (Gregoire & Smith, 1975;MacDonnell & Flynn, 1966;Welle & Coover, 1978), reduced the percentage of animals that attacked the conspecific or the mouse.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These experiments demonstrate that trigeminal somatosensation is critical for the initiation and normal execution of maternal aggression in lactating rats, regardless of previous experience with the treatment or with fighting. Our results extend to maternal aggression in rats previous findings on hypothalamically induced biting in cats (MacDonnell & Flynn, 1966) and on shock-induced fighting (Thor, 1976;Thor & Ghiselli, 1975a;Thor et al, 1974), apomorphineinduced group fighting (Thor & Ghiselli, 1975b), and mousekilling (Gregoire & Smith, 1975;Thor & Ghiselli, I975b;Welle & Coover, 1978) in male rats. Trigeminal desensitization, either acutely with local anesthesia (Thor & Ghiselli, 1975a, 1975bThor et al, 1974;this report) or chronically with lesions (Gregoire & Smith, 1975;MacDonnell & Flynn, 1966;Welle & Coover, 1978), reduced the percentage of animals that attacked the conspecific or the mouse.…”
Section: Discussionsupporting
confidence: 87%
“…Olfactory functioning is not adversely affected by perioral anesthesia (Kenyon et al, 1981) or vibrissal-pad destruction (Thor, 1976), nor are the effects of perioral anesthesia on pup retrieval due to masseter muscle dysfunction, vibrissae paralysis, akinesia, or systemic effects of Lidocaine (Kenyon et al, 1981(Kenyon et al, , 1983. Furthermore, the decreased likelihood and intensity of biting during trigeminal desensitizations are not mediated by motor impairments of the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas blinded rats fought at control levels in a shock situation, anosmic and devibrissaed pairs fought less, and olfactory bulbectomized animals showed an increase in mouse killing (cf. Bugbee & Eichelman, 1972;Ghiselli & Thor, 1975;Thor, 1976). Moreover, it has been demonstrated that shock-induced aggression is separable from territorial aggression in rats in terms of the differential influence of hypothalamic lesions on these two response types (Adams, 1971) and the differing behavioral profiles of intact animals across the two situations (Blanchard, Blanchard, & Takahashi, 1978).…”
Section: University Of Wisconsin-madisonmentioning
confidence: 99%
“…Our findings on the role of shrew whiskers in prey capture go well with a large body of literature suggesting a more general role of whiskers in attacks and aggressive behaviors. In rats whisker are required in attacks on mice (Thor and Ghiselli, 1975 ), play a significant role in controlling maternal aggression (Kolunie and Stern, 1990 ) and both in aggressive and non-aggressive social behaviors (Thor, 1976 ; Blanchard et al, 1977 ; Sarna et al, 2000 ; Brecht and Freiwald, 2011 ; Wolfe et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%